Augmented Reality: A Systematic Literature Review and Future Research Prospects in Digital Marketing - Bakar, Isa (Journal of Islamic Economics Perspectives, 2023)
To keep up with the new developments of the industrial revolution 4.0, aspects of modern society's life are increasingly strengthened by the combination of digital technology and reality. Augmented reality is a technology that overlays computer-generated images on a user's view of the real world. However, information about augmented reality in the context of digital marketing is still lacking, so it needs to be found to identify needs in research. Therefore, by conducting a systematic review of the literature, this article attempts to answer a key research question: What are the research gaps in augmented reality in digital marketing? This study is a review of the 5-year publication period from 2018 to 2022.